Maternal Congenital Aortic Stenosis-Successful Management of Pregnancy - Williams, Emily M; Daming, Tara N; Hostetter, Sarah; Florio, Karen; Grodzinsky, Anna; Lee, John; Magalski, Anthony; Rader, Valerie; Schmidt, Laura (Cardiology and Cardiovascular Medicine, 2020)
Aortic stenosis provides a unique management challenge during pregnancy and has historically been associated with a high maternal mortality risk. We describe our experience with pregnancies in patients with aortic stenosis at a single center over a 13 year period. When managed by an experienced, multidisciplinary, cardio-obstetrics team, these pregnancies are more likely to reach term with good outcomes.